PENGARUH DANA ALOKASI UMUM (DAU) DAN DANA BAGI HASIL (DBH) TERHADAP PENGALOKASIAN BELANJA MODAL DI KABUPATEN CILACAP - Yulian, Tri Nurindahyanti; Sari, Fuji Windya (JURNAL EKONOMI, 2018)
This research was conducted with the aim of analyzing the effect of the GeneralAllocation Fund (DAU), Revenue Sharing Funds (DBH) on the allocation of CapitalExpenditures. The researcher conducted research in Cilacap Regency and used secondarydata in the form of Budget Realization Reports from 2011 to 2017.Testing the hypothesis in this study using multiple linear regression analysis. Theresults showed that partially the DAU and DBH had an effect on the allocation of capitalexpenditure. Simultaneously DAU and DBH also affect the allocation of capital expenditure.Keywords: DAU, DBH, Capital Expenditure